Green : Architecture Now! - Jodidio, Philip; Kobler, Florian; Wachendorf, Ute; Koper, Kristina Brigitta; Altmeppen, Sonja; Gayring, Mischa; Bosser, Jacuqes; Eichwede, Birgit; Sense/Net, Andy Disl (Cologne : Taschen, 2009)
Buildings are among the heaviest consumers of natural resources and account for a significant portion of the greenhouse gas emissions that affect climate change. This book explains the principles of green architecture, showing how the world's leading exponents are tackling this pressing issue
Includes English, German and French languages
Includes bibliography and indexes
Keywords: Sustainable architecture; Sustainable buildings -- Design and construction; Sustainable architecture -- Case studies; Architecture, Modern -- 21st century; Architects -- Biography